A water-soluble acrylic photoresist

By introducing halogen substituents into water-soluble photoresist and building a cross-linked network three-dimensional structure, the problem of insufficient halogen effect transmission in the prior art is solved, the acid resistance and acid film retention rate are significantly improved, and high Properties of resin film formation.

CN118778361BActive Publication Date: 2024-12-20GUANGDONG KEYOU MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410834941.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-26
Publication Date
2024-12-20
Estimated Expiration
2044-06-26

AI Technical Summary

Technical Problem

When existing water-soluble photoresist introduces halogen substituents into polymers, the electron-absorbing and induction effects of halogen cannot be effectively transmitted to the main chain, resulting in insufficient etch resistance and unstable spatial structure of the polymer. .

Method used

Modified acrylic quaternary copolymer resin, by introducing halogen substituents on the main chain and using azobisisobutyronitrile as an initiator for polymerization, a cross-linked network three-dimensional structure is formed to enhance the halogen group and the main chain. The linkage improves the acid resistance and stability of the polymer.

Benefits of technology

The acid resistance and acid film retention rate of polymer compounds are significantly improved, forming a dense and stable resin film with excellent film forming properties and film thickness uniformity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004912899860000051
    Figure BDA0004912899860000051
  • Figure BDA0004912899860000061
    Figure BDA0004912899860000061
  • Figure BDA0004912899860000071
    Figure BDA0004912899860000071
Patent Text Reader

Abstract

The present invention provides a water-soluble acrylic photoresist for processing semiconductor devices and electronic components in the photolithography process. The photoresist adopts a modified acrylic tetrapolymer resin as a resin component, wherein the first monomer is a styrene derivative containing halogen, the second monomer is an N-hydroxy-5-norbornene-2,3-dicarboximide derivative, the third monomer is a modified styrene compound, and the fourth monomer is (meth)acrylic acid. Its cross-linked network stereoscopic structure enables the water-soluble acrylic photoresist disclosed by the present invention to maintain water solubility while providing excellent etching resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an etching resist, in particular to a water-soluble acrylic acid photoresist. Technical Background

[0002] Photoresist refers to an etching-resistant thin film material whose solubility changes when exposed to light or radiation such as ultraviolet light, deep ultraviolet light, electron beam, ion beam, and X-ray. It is a key material in the photolithography process and is mainly used in the fine graphic processing of integrated circuits and discrete semiconductor devices.

[0003] Photoresists can be divided into water-soluble and water-insoluble according to their solubility. Among them, water-soluble photoresists are favored by customers due to their good water solubility. Therefore, with the gradual improvement of processing precision requirements, higher requirements are constantly being placed on the performance of photoresists. Therefore, it is necessary to develop a water-soluble acrylic photoresist that can form a uniform thin film layer and has strong etching resistance.

[0004] Theoretically, monomers containing halogens can have the technical effect of increasing the etching resistance of photoresists. The prior art introduces halogens into monomers of photoresist polymers, but the halogen substituents are connected to the main chain of the skeleton through a benzene ring. The large π bond of the benzene ring conjugates the electron-withdrawing effect of the halogen on the benzene ring, and further makes the inductive effect of the halogen group transmitted through the σ bond only act on the benzene ring, and cannot be transmitted to the carbon atoms of the polymer main chain, so that its performance still has room for improvement; at the same time, in the spatial structure of the polymer, the halogen-containing substituent monomers are still in chain-like links on the main chain of the polymer skeleton, so there is still room for improvement in the spatial link structure of the polymer. Summary of the invention

[0005] In view of the limitations of the above-mentioned existing methods, the purpose of the present invention is to provide a water-soluble acrylic photoresist to solve one or more technical problems existing in the prior art and at least provide a beneficial choice or create conditions.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A water-soluble acrylic photoresist, comprising the following materials: 5-10 parts by weight of a modified acrylic tetrapolymer resin and 10-50 parts by weight of an auxiliary solvent;

[0008] The structure of the modified acrylic acid-based four-element copolymer resin comprises: a first monomer, a second monomer, a third monomer, and a fourth monomer, and the molar mass ratio thereof is 1:1:1:1 to 1:1:1:2;

[0009] The preparation scheme of the modified acrylic acid tetrapolymer resin is as follows:

[0010] S101, the first monomer and the second monomer are polymerized by a free radical initiator in an oxygen-free environment to obtain a precursor polymer A;

[0011] The specific preparation method of the precursor polymer A is as follows: the first monomer and the second monomer are added to the reactor in a molar ratio of 1:1, and an appropriate amount of N,N-dimethylformamide is used to dissolve them. It should be noted that during the preparation process, high-purity inert gases, such as nitrogen or argon, should be used multiple times for deoxygenation. After the initiator azobisisobutyronitrile is added, deoxygenation is required again, the reactor is evacuated and sealed, and the temperature is controlled at 65 degrees Celsius for 48 hours to 72 hours. The reactants in the bottle are then taken out, cooled to room temperature, a large amount of deionized water is added, the precipitate is filtered and further washed with deionized water, and then placed in a vacuum drying oven, the temperature is set to 60 degrees Celsius for vacuum drying, and the duration is 5 hours to finally obtain the precursor polymer A.

[0012] S102, heating the precursor polymer A and the third monomer at 160-185 degrees Celsius for 12-24 hours to obtain a precursor polymer B;

[0013] The specific preparation method of the precursor polymer B is as follows: the precursor polymer A and the third monomer of equal mass are added into a reaction container, placed in an oven at a temperature of 180-190 degrees Celsius, heated for 12 hours, and cooled to room temperature to obtain the precursor polymer B.

[0014] S103, the precursor polymer B and the fourth monomer are polymerized at 65-85 degrees Celsius with azobisisobutyronitrile as an initiator. After the reaction is completed, the temperature is controlled at 25-45 degrees Celsius, and a stereo cross-linking agent is added to polymerize to obtain the target polymer, that is, a modified acrylic acid-containing tetrapolymer resin.

[0015] Furthermore, the first monomer is a halogen-containing styrene derivative, including p-acetoxyphenylvinyl chloride, p-acetoxyphenylvinyl bromide, and p-acetoxyphenylvinyl fluoride.

[0016] Due to the introduction of halogen-containing monomers, a more uniform and thorough polymer halogenation effect is achieved at the monomer level of such a tetrapolymer photosensitive resin in the polymer compound, so that the tolerance to chemicals brought about by the polymer halogenation effect is more significantly changed, thereby improving the acid resistance of the polymer compound and improving the acid decomposition film retention rate of the polymer compound; and the halogen introduced in the present invention is on the side chain of the polymer main chain, which is closer to the main chain, so the field effect brought about by the strong electronegativity of the halogen group will form a strong polarity on the carbon atoms of the polymer chain, and the strong polar molecules have stronger chemical resistance, thereby more significantly affecting the stability of the polymer, that is, further increasing the acid decomposition film retention rate.

[0017] Furthermore, the second monomer is an N-hydroxy-5-norbornene-2,3-dicarboximide derivative, including N-(4-acryloxybenzoyloxy)-5-norbornene-2,3-dicarboximide, N-(4-methacryloxybenzoyloxy)-5-norbornene-2,3-dicarboximide, N-acryloxy-5-norbornene-2,3-dicarboximide, and N-methacryloxy-5-norbornene-2,3-dicarboximide.

[0018] Furthermore, the third monomer is a modified styrene compound, including p-hydroxystyrene, p-methoxystyrene, p-methylstyrene, p-chlorostyrene, 3-methylstyrene, p-bromostyrene, p-chloromethylstyrene, and 4-isopropylstyrene.

[0019] Furthermore, the fourth monomer is (meth)acrylic acid, which includes acrylic acid and methacrylic acid.

[0020] Furthermore, the preparation method of the first monomer is: dihaloethylene and acetoxystyrene are subjected to olefin metathesis reaction by catalyst and ultrasonic catalysis reaction, so as to obtain the corresponding halogenated compound, which is the first monomer.

[0021] Furthermore, the document DOI:10.1126 / science.aaf4622 reports a molybdenum-containing catalyst and a method for synthesizing a first monomer compound. However, due to its long reaction time and low yield, it is not economical in actual production and is not conducive to production.

[0022] After research, it was found that the above-mentioned catalyst can be assisted by an ultrasonic reactor to enable the reaction system with originally low activity to obtain the mechanical force of ultrasonic oscillation, and the chemical bond between the metal and its ligand can be destroyed by mechanical force, so that the ligand is dissociated and the catalyst in a stable state is activated, so that the above-mentioned catalyst can catalyze the reaction system to cross the energy barrier faster in the system, and the olefin metathesis reaction can proceed smoothly, thereby obtaining the first monomer.

[0023] Furthermore, the power of the ultrasonic reactor should not be less than 200W.

[0024] Furthermore, the auxiliary solvent comprises, by weight, 1-10 parts of photoacid, 0.1-1 parts of organic base and 50-80 parts of solvent.

[0025] Furthermore, the auxiliary solvent includes carbohydrazide, malonic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide and adipic acid dihydrazide as stereo cross-linking agents.

[0026] Furthermore, the stereo crosslinking agent allows the acetoxy group on the first monomer of the modified acrylic tetrapolymer resin in the water-soluble acrylic photoresist to form a covalent bond with the stereo crosslinking agent, thereby connecting the polymer main chains of different modified acrylic tetrapolymer resins to form a crosslinked network stereostructure.

[0027] Furthermore, when the stereo cross-linking agent is added, the temperature of the stereo cross-linking agent and the reaction system is 25-45 degrees Celsius.

[0028] Since the steric hindrance of the substituent group of the second monomer on the polymer main chain of the modified acrylic tetrapolymer resin is relatively large, and its electron cloud will affect the effect of the cross-linking agent, carbohydrazide, malonic acid dihydrazide, succinic acid dihydrazide, and glutaric acid dihydrazide have poor effects during the reaction due to their short chain lengths, and the cross-linked network stereoscopic structure formed by them has poor stability. Therefore, stereoscopic cross-linking agents with similar structures having longer carbon chains have better stability. Therefore, the preferred stereoscopic cross-linking agent in the present invention is adipic acid dihydrazide.

[0029] Furthermore, the photoacid includes any one of triphenylsulfonium salt, tri-p-tolylsulfonium salt, tri-p-tert-butylphenylsulfonium salt, tri-p-octylphenylsulfonium salt, di-p-octylphenyliodonium salt, and di-p-tolyliodonium salt, or a combination of two or more thereof; the coordinating anion in the sulfonium salt is any one of trifluoromethylsulfonate, perfluorobutylsulfonate, p-tolylsulfonate, and naphthalenesulfonate.

[0030] Furthermore, the organic base includes any one of triethanolamine, triethoxyethanolamine, and tetramethylammonium hydroxide.

[0031] Furthermore, the solvent includes any one of water, propylene glycol methyl ether acetate, propylene glycol monoacetate, propylene glycol monoethyl ether, propylene glycol methyl ether acetate, butyl acetate, neopentyl acetate, ethyl lactate, methyl ethyl ketone, and methyl isobutyl ketone, or a combination of two or more of them in any proportion.

[0032] Furthermore, other auxiliary additives include common additives for resists such as dyes.

[0033] The beneficial effects of the present invention are:

[0034] The water-soluble acrylic photoresist provided by the present invention has excellent various properties because it adopts a modified acrylic tetrapolymer resin containing a halogen substituent at the ortho position of the main chain skeleton. The reason is that the halogen substituent is closer to the main chain of the copolymer in the modified acrylic tetrapolymer resin, so that its inductive effect and electron-withdrawing effect directly act on the main chain, so that the electron cloud density of the main chain is increased and the chemical property is more stable. At the same time, a stereo crosslinking agent is used to connect different polymer main chains in the modified acrylic tetrapolymer resin to form a crosslinked network stereostructure. The crosslinked network stereostructure uses the first monomer containing a halogen substituent at the ortho position of the main chain as the stereo bonding center connected to the main chain, and is more stable in chemical structure. Therefore, the water-soluble acrylic photoresist can form a dense and stable resin film in actual use, and has reliable film-forming performance, film thickness uniformity and more excellent acid decomposition film retention rate. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments to clearly and completely describe the concept, specific structure and technical effects of the present invention, so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments and features in the embodiments of this application can be combined with each other without conflict.

[0036] 1. Preparation of modified acrylic acid tetrapolymer resin (Examples 1-12):

[0037] 0.1 mol of dihalogenated vinyl and 0.1 mol of acetoxystyrene were added to an ultrasonic reactor (model H43-1000D), the solvent was 300 ml of tetrahydrofuran, and then 0.01 mol of trimethylsilyl-substituted cyclopentadienyl dicarbonyl molybdenum ring carbene complex was added as a catalyst. The reactor power was set to 300 watts to carry out olefin metathesis reaction, thereby obtaining the corresponding halogenated compound, which is the first monomer.

[0038] The selected first monomer and the second monomer are added to the reactor in a molar ratio of 1:1, and an appropriate amount of N,N-dimethylformamide is used to dissolve them. It should be noted that during the preparation process, high-purity inert gases, such as nitrogen or argon, should be used multiple times for deoxygenation, and after the initiator azobisisobutyronitrile is subsequently added, deoxygenation is required again, the reactor is evacuated and sealed, and the temperature is controlled at 65 degrees Celsius for 48 hours to 72 hours. The reactants in the bottle are then taken out, cooled to room temperature, a large amount of deionized water is added, the precipitate is filtered and further washed with deionized water, and then placed in a vacuum drying oven, the temperature is set to 60 degrees Celsius for vacuum drying, and the duration is 5 hours. Subsequently, the precursor polymer A and an equal amount of the third monomer are added to the reaction vessel, placed in an oven at a temperature of 180-190 degrees Celsius, heated for 12 hours, and cooled to room temperature to obtain a precursor polymer B. The precursor polymer B and the fourth monomer (meth) acrylic acid are polymerized at 65-85 degrees Celsius with azobisisobutyronitrile as an initiator, and then the resultant is cooled to 40 degrees Celsius, and adipic acid dihydrazide is added for stereo crosslinking to obtain the target polymer, i.e., a photosensitive resin containing a modified acrylic tetrapolymer, with a molecular weight of 12000-100000 and a molecular weight distribution index of 1.5-2.7. The specific formulation of the modified acrylic tetrapolymer is shown in Table 1.

[0039] Comparative Example 1: The steps are the same as those in Example 1, but adipic acid dihydrazide is not added for stereo cross-linking reaction. The preparation table is shown in Table 1.

[0040] Comparative Example 2: The steps are the same as those in Example 1, but the synthesis of the precursor polymer B is considered complete, and adipic acid dihydrazide is not added for stereo cross-linking reaction. The formulation is shown in Table 1.

[0041] Comparative Example 3: The steps are the same as those in Example 1, but polymerization is not performed using the first monomer. The second monomer is directly used as the starting point for polymerization to obtain a precursor polymer B, which is polymerized with (meth)acrylic acid. At the same time, adipic acid dihydrazide is not added for stereo cross-linking reaction to obtain Comparative Example 3.

[0042] Table 1. Sample polymer formulation

[0043]

[0044]

[0045]

[0046] 2. Preliminary test of the performance of modified acrylic tetrapolymer resin:

[0047] The examples and comparative examples mentioned above were used as samples.

[0048] Film-forming performance test: Take 0.5g of the sample and dissolve it in 5ml of deionized water to obtain a polymer solution. Filter it with a 0.25μm ultrafiltration membrane, and then use a coater to apply it to a single crystal silicon wafer at a speed of 3000-6000r / min. Then dry it on a 90-degree Celsius baking tray for 10 minutes. Use an optical microscope to observe whether the polymer film is in good condition. The specific standards are whether there are cracks and peeling, and whether there are solid particles. If there are no cracks, peeling, or solid particles, it is considered good, otherwise it is poor.

[0049] Film thickness performance test: Use Bruker DektakXT step profiler to test the sample. The monitoring item is the uniformity of film thickness. The judgment standard is: the film thickness fluctuation within 0.02μm is considered qualified, and beyond this range is considered unqualified.

[0050] The document DOI:10.1117 / 12.241851 reports that ammonium trifluoromethanesulfonate is relatively stable at room temperature, but when heated to a higher temperature, it will decompose to produce trifluoromethanesulfonic acid, which is similar to the reaction in photoresist. Therefore, the thermal decomposition of ammonium trifluoromethanesulfonate to produce acid can be used to replace the photoinduced acid production in actual photoresist, thereby more closely simulating the actual situation under limited production and research and development conditions to test the film retention rate of the sample.

[0051] Acid decomposition film retention rate test: add 1% of the mass of ammonium trifluoromethylsulfonate to the sample, dissolve it, filter it with a 0.25μm ultrafiltration membrane, and then use a glue spreader to apply it to a single crystal silicon wafer, bake it at 70 degrees Celsius, 80 degrees Celsius, and 90 degrees Celsius for 5 minutes each, and use a step meter to test the thickness of the film after cooling, which is recorded as H1; then put it into a 2.38% tetramethylammonium hydroxide solution and soak it for 3 minutes, take it out and rinse it with deionized water, dry it at 90 degrees Celsius, and then test the thickness of the film, which is recorded as H2. The acid decomposition film retention rate is

[0052] Table 2. Performance test results

[0053]

[0054]

[0055] According to Table 2, the film-forming effects of the embodiments are better than those of the comparative examples, indicating that the fourth monomer provides good water solubility, so that the polymer can smoothly form a film in a system with water as a solvent and maintain good performance; the acid decomposition film retention rates of Examples 1-12 are all over 80%, which is greatly improved compared with Comparative Examples 1-2, and is significantly better than Comparative Example 3. The common difference between the embodiments and the comparative examples is whether a stereo cross-linking agent is used to construct a cross-linked network stereo structure. In the data, Comparative Example 1 has the same formula as Example 2, but the film-forming performance is significantly reduced, indicating that in the absence of a stereo cross-linking agent, the lack of a stereo cross-linking agent successfully induces a cross-linking reaction, so that a cross-linked network stereo structure is formed in the modified acrylic tetrapolymer resin; it indicates that the first monomer in the technical solution provided by the present invention has a significant improvement in the acid decomposition film retention rate.

[0056] Example 13

[0057] The acetoxyphenylvinyl chloride-co-N-p-methacryloyloxybenzoyloxy-5-norbornene-2,3-dicarboximide-co-p-chloromethylstyrene-co-(methyl)acrylic acid of Example 2 with the highest acid decomposition film retention rate is selected as the modified acrylic tetrapolymer resin component in the water-soluble acrylic photoresist, 10g is weighed, placed in a 500ml polytetrafluoroethylene beaker, and 80g of auxiliary solvent is added. The auxiliary solvent composition is: 0.2 tris (4-tert-butylphenyl) sulfonium trifluoromethanesulfonate, 0.3g tetramethylammonium hydroxide, 79.5g deionized water. The mixture is fixed on an oscillator, shaken and mixed for 24 hours, and filtered with a 0.5μm filter membrane. The water-soluble acrylic photoresist obtained after filtration is the water-soluble acrylic photoresist described in the present application.

[0058] Although the description of the present invention has been quite detailed and has been described in particular with respect to several described embodiments, it is not intended to be limited to any of these details or embodiments or any particular embodiment, so as to effectively cover the intended scope of the present invention. In addition, the present invention is described above with the embodiments foreseeable by the inventors, and its purpose is to provide a useful description, and those non-substantial changes to the present invention that are not currently foreseen may still represent equivalent changes of the present invention.

Claims

1. A water-soluble acrylic photoresist, characterized in that: The composition of the water-soluble acrylic photoresist includes the following substances: by weight, 5-10 parts of a modified acrylic tetrapolymer resin and 10-50 parts of an auxiliary solvent; The structure of the modified acrylic tetrapolymer resin comprises: a first monomer, a second monomer, a third monomer, and a fourth monomer, and the molar mass ratio thereof is 1:1:1:1 to 1:1:1:2; The preparation scheme of the modified acrylic acid tetrapolymer resin is as follows: S101, the first monomer and the second monomer are polymerized by a free radical initiator in an oxygen-free environment to obtain a precursor polymer A; S102, heating the precursor polymer A and the third monomer at 160-185 degrees Celsius for 12-24 hours to obtain a precursor polymer B; S103, the precursor polymer B and the fourth monomer are subjected to polymerization reaction at 65-85 degrees Celsius with azobisisobutyronitrile as an initiator, and after the reaction is completed, the temperature is controlled at 25-45 degrees Celsius, and a three-dimensional cross-linking agent is added to carry out a cross-linking reaction to obtain a target polymer, i.e., a modified acrylic acid-containing tetrapolymer resin; Wherein, the stereo cross-linking agent is adipic acid dihydrazide; Wherein, the first monomer is a styrene derivative containing halogen and acetoxy, including p-acetoxyphenylvinyl chloride or p-acetoxyphenylvinyl bromide; Wherein, the second monomer is an N-hydroxy-5-norbornene-2,3-dicarboximide derivative, including N-(p-acryloxy)benzoyloxy-5-norbornene-2,3-dicarboximide, N-(p-methacryloxy)benzoyloxy-5-norbornene-2,3-dicarboximide, N-acryloxy-5-norbornene-2,3-dicarboximide or N-methacryloxy-5-norbornene-2,3-dicarboximide; Wherein, the third monomer is a modified styrene compound, including p-hydroxystyrene, p-methoxystyrene, p-methylstyrene, p-chlorostyrene, 3-methylstyrene, p-bromostyrene, p-chloromethylstyrene or 4-isopropylstyrene; The fourth monomer is (meth)acrylic acid, which includes acrylic acid and methacrylic acid.

2. A water-soluble acrylic photoresist according to claim 1, characterized in that: The acetoxy group on the first monomer of the modified acrylic tetrapolymer resin in the water-soluble acrylic photoresist forms a covalent bond with the stereo crosslinking agent, so that different polymer main chains in the modified acrylic tetrapolymer resin are connected to each other by the crosslinking agent to form a crosslinked network stereo structure.

3. The water-soluble acrylic photoresist according to claim 1, characterized in that: The auxiliary solvent comprises: by weight, photoacid: 1-10 parts; Organic base: 0.1-1 part; Solvent: 50-80 parts; other additives 0-5 parts.

4. An electronic device, characterized in that: The water-soluble acrylic photoresist according to claim 1 is used in the manufacturing process.